2023
DOI: 10.3390/nu15041049
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Ameliorates Myocardial Ischaemia/Reperfusion Injury by Improving Mitochondrial Function via Immunoproteasome-PP2A-AMPK Signalling

Abstract: Cardiac ischaemia/reperfusion (I/R) injury causes cardiomyocyte apoptosis and mitochondrial dysfunction. Ursolic acid (UA), as a pentacyclic triterpenoid carboxylic acid, exerts several bioactivities in animal models of different diseases, but the preventive role of UA in I/R-induced myocardial dysfunction remains largely unknown. Male wild-type mice were pre-administered with UA at a dosage of 80 mg/kg i.p. and then subjected to cardiac I/R injury for 24 h. Cardiac function and pathological changes were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…Although numerous proteasome inhibitors, such as bortezomib (velcade), have been developed and can be safely administered to treat blood tumours with few side effects, very few molecules have been identified as potentially effective proteasome enhancers to date. Recently, we identified that ursolic acid (UA) is a new enhancer of immunoproteasome subunit expression that can prevent cardiac I/R injury [ 14 ]. Furthermore, several signalling mediators, such as STAT and cAMP-response element-binding protein (CREB), can increase immunoproteasome subunit transcription [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous proteasome inhibitors, such as bortezomib (velcade), have been developed and can be safely administered to treat blood tumours with few side effects, very few molecules have been identified as potentially effective proteasome enhancers to date. Recently, we identified that ursolic acid (UA) is a new enhancer of immunoproteasome subunit expression that can prevent cardiac I/R injury [ 14 ]. Furthermore, several signalling mediators, such as STAT and cAMP-response element-binding protein (CREB), can increase immunoproteasome subunit transcription [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20 μg lysate proteins were added to 50 μl of reaction buffer that contains three fluorogenic peptides, including Z -nLPnLD-Glo™ (40 μM), Z -LRR-Glo™ (30 μM), or Suc-LLVY-Glo™ (40 μM), and reacted at RT for 10 min. Proteasomal activities (caspase-like, trypsin-like, and chymotrypsin-like) in the tissues were evaluated using Proteasome-Glo assay kit following the manufacturer's instructions (Promega) as previously reported [ 14 ]. The fluorescence intensities were measured with an automatic microplate reader (Spark).…”
Section: Methodsmentioning
confidence: 99%
“…36 Wongam, a licoricederived natural product, suppresses IL-1beta-promoted chondrocyte hypertrophy and nuclear translocation of histone deacetylase 4 (HDCA4), downregulated by PP2A inhibitor okadaic acid. 37 This result suggests that wongam upregulates PP2A ( Granulocyte-macrophage Nodularin 49 Liver cells Ursolic acid 50 Heart Chaetomellic anhydride 51 7-Deoxy-okadaic acid 52 Dinophysistoxin-4 53 Hipposulfate C 54 Halisulfate-7 54 Irregularasulfate 54…”
Section: Non-cancer Studies For Pp2a-inducing Natural Productsmentioning
confidence: 99%
“…48 Ursolic acid upregulates catalytic caspase-, trypsin-, and chymotrypsin-like proteasomes of heart tissues to reduce myocardial ischemia/reperfusion injury, enhancing ubiquitinated PP2A degradation and mitochondrial biosynthesis. 50 Dinophysistoxin-4, 53 nonadrides, and chaetomellic anhydride 51 exhibit PP2A-inhibitory effects. An okadaic acid-derived synthetic marine natural product, 7-deoxy-okadaic acid, is a potential PP2A inhibitor.…”
Section: Pp2a-inhibiting Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation